Selective Localization of Hierarchically Assembled Particles to Plasma Membranes of Living Cells. Issue 5 (28th January 2019) - Misra, Asish C.; Park, Tae‐Hong; Carney, Randy P.; Rusciano, Giulia; Stellacci, Francesco; Lahann, Joerg
Abstract: Particles that preferentially partition to a specific cellular subunit, such as the nucleus, mitochondria, or the cytoskeleton, are of relevance to a number of applications, including drug delivery, genetic manipulation, or self‐assembly. Here, hierarchical assemblies of fully synthetic particles that selectively localize to the plasma membrane of mammalian cells are presented. A multimodal approach is used to create assemblies of polymer‐based carrier particles with amphiphilic gold nanoparticles immobilized on one hemisphere. These assemblies persist in the plasma membrane of cells for several days and undergo rearrangements and clustering, typically considered to be hallmarks of membrane‐bound receptors. Abstract : Assemblies of polymer‐based carrier particles with amphiphilic gold nanoparticles selectively immobilized on one hemisphere are shown to selectively localize to the plasma membranes of mammalian cells.